Investigation of traffic interaction in ISDN networks : significance of holding times - Siddiqui, Junaid; Murch, Alan; Sharma, A.B.; Lochmann, Steffen; O'Farrell, Timothy; Government of Netherlands (Bangkok : Asian Institute of Technology, 1992)
The integrated services networks (as for example, N-ISDN or B-ISDN) are expected to carry, a wide variety of services. These services are to be switched using the same network. This integration of services, though advantageous economically, has some undesirable features. These services integrated over a common network may differ in their holding times. A situation may develop where long duration calls of a traffic class set up over the network links (in accordance with some routing strategy) at the time when network was not congested are still in progress during times of congestion . Such calls may result in an increase in call blocking probability. This thesis investigated the interaction between two traffic classes with different call durations (mean holding time as well as holding time distributions), proportions of traffic and non-coincident busy hours for different routing strategies. The basis of this study was the evaluation of the call blocking probability of short duration service class. This investigation was based upon computer simulation. From the results of the simulation, it is found that short duration traffic class suffers higher call blockings when the long duration holding times are generated in accordance with either negative exponential or uniform distributions when compared to constant distribution . The effect of routing suggests that it is more advantageous for short duration class to route the calls with non alternative routing strategies, rather than alternately route them.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology,1992
Keywords: Telecommunication -- Traffic